2021
DOI: 10.1002/ehf2.13694
|View full text |Cite
|
Sign up to set email alerts
|

A proposed strategy for anticoagulation therapy in noncompaction cardiomyopathy

Abstract: Noncompaction cardiomyopathy (NCCM) is a rare condition characterized by prominent trabeculae, deep intertrabecular recesses, and a left ventricular myocardium with a two-layered structure, characterized by a spongy endocardial layer and a thinner and compacted epicardial one. NCCM can be isolated or associated with other congenital heart diseases and complex syndromes involving neuromuscular disorders and facial dysmorphisms. To date, more than 40 genes coding for sarcomeric, cytoskeletal, ion channels, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 71 publications
0
22
0
1
Order By: Relevance
“…Noncompaction cardiomyopathy (NCC) is rare genetic cardiomyopathy [ 2 ] first described in 1932 and characterized by excess trabeculae in the endocardium, affecting one or both ventricles [ 2 , 5 - 6 ]. Prevalence estimates range from 0.01% to 0.27% among patients who were referred for an echocardiogram for other workups [ 2 , 5 ]. In reference to the entire population, estimates range from 0.014% to 1.3%, with males affected more than females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Noncompaction cardiomyopathy (NCC) is rare genetic cardiomyopathy [ 2 ] first described in 1932 and characterized by excess trabeculae in the endocardium, affecting one or both ventricles [ 2 , 5 - 6 ]. Prevalence estimates range from 0.01% to 0.27% among patients who were referred for an echocardiogram for other workups [ 2 , 5 ]. In reference to the entire population, estimates range from 0.014% to 1.3%, with males affected more than females.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of NCC is thought to be due to a failure of “compaction” of the myocardium during embryogenesis [ 5 ]. The diagnosis is established most commonly via transthoracic echocardiogram and cardiac magnetic resonance imaging [ 2 ], with echocardiogram showing a ratio of greater than 2.0 between the end-systolic thickness of the compacted vs noncompacted tissue [ 7 ]. Recent reports indicate high sensitivity and specificity using a ratio of >2.3 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although DOACs showed superiority relative to VKAs in large phase III RCTs and demonstrated to be non-inferior in terms of safety, phase IV prospective observational trials aimed at verifying the safety of drugs after being placed on the market and other real-life observational studies confirmed the safety of DOACs in a daily practice setting, also fueling the progressive expansion of DOACs indication in the subgroup of patients excluded from RCTs, such as cancer patients and end-stage renal disease patients [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The XANTUS program was a prospective, observational, noninterventional study evaluating the safety of rivaroxaban used for stroke prevention in 11.121 patients with AF [ 25 ].…”
Section: Discussionmentioning
confidence: 99%